Pengaruh Strategi Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Siswa di Sekolah Menengah - Wahyu Ardias; Khairul Fajri; Gusmaneli Gusmaneli (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the impact of the Jigsaw cooperative learning strategy on student learning outcomes at the secondary school level. Using a literature review method, the research synthesizes theoretical perspectives on cooperative learning, detailed applications of the Jigsaw model, and empirical findings from previous studies that focus on its effects across cognitive, affective, and psychomotor domains. The findings indicate that the Jigsaw strategy significantly improves students’ cognitive achievements and fosters affective development such as motivation, empathy, and positive attitudes toward learning. In addition, this strategy enhances students’ social interaction skills and promotes collaborative behavior, contributing to a more inclusive and engaging classroom environment. The collaborative nature of the Jigsaw model allows students to take responsibility for their own learning while also supporting their peers, which contributes to deeper understanding and retention of the material. These outcomes suggest that the Jigsaw method is an effective instructional approach for enhancing student engagement and academic performance. The implications of this study emphasize the importance of providing professional development opportunities for teachers to effectively implement the Jigsaw strategy. Furthermore, schools are encouraged to foster a classroom climate that supports teamwork and active student participation. Overall, this review highlights the Jigsaw model as a promising pedagogical tool for improving student outcomes and fostering 21st-century skills in secondary education settings.